Efektivitas Ekstrak Nanas (Ananas comosus(L.) pada Pertumbuhan Streptococcus beta-hemolitycus - Sri Ujiani; Marhamah Marhamah (Politeknik Kesehatan Tanjung Karang, 2019)
Prevalence of Group A beta-hemolyticus Streptococcus in the upper respiratory tract in healthy children is 10-35%, and at most high, in children aged 3-15 years Career Streptococcus beta-hemolyticus Group A can cause throat infections. The use of traditional medicine in the world is part of the history of human culture for thousands of years. One of the natural ingredients that can be used as traditional medicine is pineapple. The effectiveness of pineapple (Ananas comosus (L.) extract on the growth of beta-hemolitycus Streptococcus has been carried out. The purpose of this study was to determine the effectiveness of pineapple extract (Ananas comosus (L.) on the growth of Streptococcus beta-hemolitycus. This study was an experimental laboratory study) pure in vitro. In this study, the inhibitory and killing power of Ananas comosus (L.) extract against the growth of Streptococcus β haemolyticus at various concentrations of 0.5%; 1%; 2%; 4%; 8%; 10%; 20%; 30%; 40%; 50%; 60%; 70%; 80%; 90%; 100% .. The research was conducted at the Lampung Provincial Health Laboratory Hall conducted from June to November 2018. The results of the One-way Anova test obtained p-value=0,000 so that p-value<0.05 which means that the concentration of pineapple extract tested had an effect on growth of Streptococcus beta hemolyticus bacteria and the results of the Least Significant Difference (LSD) or Post hoc LSD (Least Significance Different) test (p-value<0,05) showed that pineapple extract was effective in inhibiting and killing germs of Streptococcus β haemolyticus at a concentration of 8%.